Innovation Policy through Online Single Submission Program in Licensing Services in Indragiri Hulu District - Tasha Amelia; Zaili Rusli; Adianto Adianto (Jurnal Mantik, 2021)
This research is motivated by the availability of inadequate infrastructure, the introduction of the community to the Online Single Submission program which is still low and the mastery of officers over this program at the Office of Investment and One Stop Integrated Services, Indragiri Hulu Regency. In the Online Single Submission innovation policy, it is still not running as its main goal, namely the ease of obtaining permits for business actors without having to come to the office. There is still no basic infrastructure support, public knowledge and related service officials regarding this program so that its use is still not optimal, of course this creates obstacles in the course of implementing the Online Single Submission program. The purpose of this study is to explain the Innovation Policy Through the Online Single Submission Program in Licensing Services in Indragiri Hulu Regency. The type of research chosen is qualitative research with a descriptive case study approach. Data collection techniques were carried out through interviews, observation, and documentation. This study determines the research informants as a source of information to obtain the required data. Informants in this study are people who know the research problem in depth. The number of informants in this study were 9 people. The results of the study found that public ignorance of the Online Single Submission program lacked promotion and socialization to the community in terms of the criteria for developing a conducive general framework, strengthening institutions and supporting science and technology/R&D capacity and developing the ability to absorb business activities of the community, foster collaboration for innovation and increase the diffusion of innovation. , encourage a culture of innovation, develop and strengthen the integration of the advancement of regional and national innovation systems and industrial clusters as well as alignment with global developments. The inhibiting factors are the lack of intensive and massive socialization and promotion activities, public trust and half implemented.